Composite oil well cement paste lightening agent as well as preparation method and application thereof

The composite oil well cement slurry weight-reducing agent prepared by forming core-shell hollow microspheres with modified resin and active silicon aluminum oxide, combined with nano-reinforcing materials and coupling agents, has high strength and high temperature stability at low density. It solves the problems of weak interfacial bonding and unstable performance under high temperature environment in the existing technology and is suitable for sealing low-pressure and easily leaking formations.

CN121672969APending Publication Date: 2026-03-17BEIJING OILCHEMLEADER SCI TECH DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511919106.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-18
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing composite weight-reducing agents suffer from weak interfacial bonding, unstable performance under high-temperature conditions, and poor compatibility with cement paste admixtures, making it difficult to simultaneously achieve ultra-low density, high strength, and good high-temperature stability.

Method used

A composite oil well cement slurry weight-reducing agent was prepared by using modified resin and active silicon aluminum oxide to form core-shell hollow microspheres, combined with nano-reinforcing materials and coupling agents, through the sol-gel method, which enhances interfacial bonding and high-temperature stability.

Benefits of technology

It achieves high compressive strength, flexural strength and high temperature stability of cement slurry with low density, adapts to a wide temperature range, and is well compatible with a variety of admixtures, solving the problem of sealing low-pressure and easily leaking strata.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a composite oil well cement paste lightening agent as well as a preparation method and application thereof. The composite oil well cement paste lightening agent comprises the following components in parts by weight: 20-40 parts of hollow microspheres, 15-25 parts of modified resin, 25-30 parts of a nano reinforcing material and 3-8 parts of a coupling agent, wherein the modified resin is prepared by reacting bisphenol A type epoxy resin with active silicon-aluminum oxide. Through the synergistic effect of a plurality of components, the prepared cement paste has enough compressive strength, breaking strength and high-temperature stability while being relatively low in density, and can be well compatible with a plurality of additive systems. According to the lightening agent, the density of the cement paste can be reduced to 1.20-1.60 g / cm < 3 >, and meanwhile, the compressive strength (24h is greater than or equal to 15MPa) of set cement and the stability (the density difference is less than or equal to 0.03 g / cm < 3 >) of the paste are ensured. The preparation method is simple in process, low in cost and particularly suitable for complex well cementation operation of low-pressure easily-leaked stratums, long sealing sections and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of oilfield cementing engineering materials technology. Specifically, it relates to a composite oil well cement slurry weight-reducing agent, its preparation method, and its application. Background Technology

[0002] In oil and gas field cementing operations, especially in low-pressure, easily leaking formations, long cemented sections, and weak formations, conventional cement slurry (with a density typically of 1.85-1.90 g / cm³) is used. 3 High pressure in the grout column often leads to formation fracturing, resulting in cement grout leakage and poor sealing performance. To solve this problem, the industry typically uses low-density cement grout technology, the core of which lies in using weight-reducing agents to lower the density of the cement grout.

[0003] Currently, commonly used light-reducing agents mainly include the following categories: (1) Beaded materials: such as hollow glass microspheres, ceramic microspheres, etc., which have the advantages of low density and high strength, but are easily broken under high pressure, resulting in an increase in cement paste density; (2) Solid light-reducing materials: such as bentonite, diatomaceous earth, microsilica, etc., although the cost is low, the density reduction is limited and will significantly reduce the strength of cement stone; (3) Chemical foaming agents: reduce density by generating bubbles, but the paste has poor stability and slow strength development.

[0004] In summary, conventional low-density cement slurry systems have low compressive strength, poor slurry stability, and a limited range for density reduction. Microspheres can be modified to have characteristics such as low breakage rate and high compressive strength. However, single weight-reducing materials are still difficult to meet multiple requirements such as density, strength, and stability. Existing technologies include the preparation of composite weight-reducing agents.

[0005] However, existing composite weight-reducing agents also have the following shortcomings: (1) weak interfacial bonding between components, making them prone to delamination; (2) unstable performance under high temperature conditions; and (3) poor compatibility with cement paste admixtures. Therefore, developing a composite weight-reducing agent that can take into account ultra-low density, high strength, good high temperature stability, and wide adaptability has become an urgent technical problem to be solved in this field. Summary of the Invention

[0006] Therefore, the technical problem to be solved by the present invention is to provide a composite oil well cement slurry weight-reducing agent, its preparation method and application, which can ensure that the cement stone has a low density while having sufficient compressive strength, flexural strength and high temperature stability.

[0007] To solve the above-mentioned technical problems, the present invention provides the following technical solution:

[0008] A composite oil well cement slurry weight-reducing agent comprises the following components in parts by weight: 20-40 parts hollow microspheres, 15-25 parts modified resin, 25-30 parts nano-reinforcing material, and 3-8 parts coupling agent;

[0009] The modified resin is prepared by reacting bisphenol A type epoxy resin with active silicon aluminum oxide.

[0010] The modified resin in the composite oil well cement slurry weight-reducing agent of this invention is prepared by reacting bisphenol A type epoxy resin with active silica-alumina oxide, wherein the active silica-alumina oxide is prepared by tetraethoxysilane (TEOS) and aluminum nitrate via a sol-gel method. The prepared active silica-alumina oxide has a large specific surface area, forming an atomically dispersed Si-O-Al three-dimensional network structure. The surface of the active silica-alumina oxide has relatively uniform active sites of silanol and aluminumol groups, which can chemically bond with the epoxy groups of the epoxy resin during the reaction process, forming a strong covalent bond connection and a core-shell structure. This enhances the interfacial bonding force between the inorganic material and the organic resin, effectively transferring stress. When the modified resin fills the voids or surface between hollow microspheres, it greatly improves the temperature resistance, compressive strength, flexural strength, and other mechanical properties of the cement paste; it also improves the bonding force between the hollow microspheres and the cement matrix, thus ensuring the reliability of the modified resin as a binder coating the surface of the hollow microspheres and as a reinforcement of the system density. Adding only bisphenol A epoxy resin can enhance its strength to some extent, but bisphenol A epoxy resin has low heat resistance, which will affect the high-temperature stability of subsequent cement grout to some extent.

[0011] The added nano-reinforcing materials further fill the micropores and improve the material density and mechanical properties; the coupling agent promotes the compatibility and dispersion stability among the components. Through the synergistic effect of multiple components, this invention produces a cement paste with low density but sufficient compressive strength, flexural strength, and high-temperature stability, and it is compatible with a variety of admixture systems.

[0012] The aforementioned composite oil well cement slurry weight-reducing agent comprises an active silica-alumina oxide with a Si-O-Al three-dimensional network structure. When this active silica-alumina oxide with its three-dimensional network structure reacts with bisphenol A type epoxy resin, the relatively uniform silanol and aluminum hydroxyl groups on its surface can bind well with the resin. The specific surface area of ​​the active silica-alumina oxide is 300~600 m² / g. 2 / g, with a pore size of 2~10nm, the pore structure of active silica alumina can effectively inhibit the expansion of cement stone cracks, improve the density of cement stone, and its large specific surface area helps to make the interface bonding with bisphenol A type epoxy resin stronger.

[0013] The aforementioned composite oil well cement slurry weight-reducing agent, wherein the active silica-alumina oxide is prepared by a sol-gel method using tetraethoxysilane (TEOS) and aluminum nitrate, wherein the mass ratio of tetraethoxysilane to aluminum nitrate is (4~6):1.

[0014] The aforementioned composite oil well cement slurry weight-reducing agent, specifically using the sol-gel method, is as follows:

[0015] S1. Tetraethoxysilane and anhydrous ethanol are mixed at a volume ratio of 1:(2~4) to obtain a precursor solution A;

[0016] S2. Mix aluminum nitrate and deionized water at a mass ratio of 1:(9~11) to obtain precursor solution B;

[0017] S3. At 30-35℃, add the B precursor solution dropwise to the A precursor solution. After the addition is complete, raise the temperature to 40-45℃ and react for 1-2 hours to obtain a sol.

[0018] S4. After pouring out the sol, allow it to stand and age at 40-45℃, then dry it at 80-120℃ to form a solid gel. Subsequently, calcine it at 600-700℃ to obtain active silicon aluminum oxide.

[0019] A sol-gel method is employed to form a uniform Si-O-Al three-dimensional network structure in solution through a hydrolysis-condensation process involving silicon and aluminum sources. The resulting material exhibits a highly uniform amorphous structure with abundant and evenly distributed active sites (silanol and aluminum hydroxyl groups). Simultaneously, this method achieves a high specific surface area and porous structure, significantly enhancing the transport and adsorption capabilities of substances. This allows the active silica-alumina oxide prepared by this method to readily form strong interfacial bonds with resins or cement slurries, exhibiting performance far superior to silica-alumina oxides bonded to resins prepared by simple mechanical mixing or conventional calcination methods.

[0020] The aforementioned composite oil well cement slurry weight-reducing agent, wherein the hollow microspheres are one or more of cenospheres, glass microspheres, and ceramic microspheres.

[0021] The aforementioned composite oil well cement slurry weight-reducing agent has hollow microspheres with a bulk density of 0.60-0.90 g / cm³. 3 The compressive strength is ≥70MPa. These hollow microspheres are filled with gas. Since the lower the bulk density, the better the effect of reducing the density of the system, the compressive strength will be greatly reduced. The hollow microspheres with the bulk density in this application can effectively reduce the density of cement paste while providing a certain compressive strength.

[0022] The aforementioned composite oil well cement slurry weight-reducing agent comprises hollow microspheres with an average particle size of 40-80 μm; modified resin with an average particle size of 10-20 μm; and nano-reinforcing materials with an average particle size of 0.01-0.1 μm. The volume ratio of the hollow microspheres, modified resin, and nano-reinforcing materials is (8-10):(1-2):(2-2.5). Based on the close packing theory, this invention optimizes the particle size distribution of three levels of particles—coarse (hollow microspheres, d50=40-80 μm), medium (modified resin fragments, d50=10-20 μm), and fine (nano-reinforcing materials, d50=0.01-0.1 μm)—to achieve the closest possible arrangement between particles. Experiments have determined that the optimal volume ratio of the three levels of particles is (8-10):(1-2):(2-2.5), enabling the weight-reducing agent to maintain low density while possessing higher compressive strength and stability.

[0023] The aforementioned composite oil well cement slurry weight-reducing agent uses a silane coupling agent, specifically γ-aminopropyltriethoxysilane or γ-glycidoxypropyltrimethoxysilane. One end of the coupling agent molecule bonds to inorganic materials (cement, microspheres), while the other end bonds to organic materials (resin), thereby improving the interfacial bonding between components and preventing delamination.

[0024] The aforementioned composite oil well cement slurry weight-reducing agent comprises a nano-reinforcing material that is a composite of nano-silica and nano-alumina, wherein the weight ratio of nano-silica to nano-alumina in the nano-reinforcing material is (1-2):1, and the specific surface area of ​​the nano-reinforcing material is ≥200 m². 2 / g. Nano-reinforcing materials fill the spaces between micron-sized particles, further optimizing the packing density and achieving close packing. At the same time, nano-silica and nano-alumina can significantly improve the long-term strength of cement stone through pozzolanic reaction during cement hydration.

[0025] A method for preparing a composite oil well cement slurry weight-reducing agent includes the following steps:

[0026] Step 1: Pretreatment of hollow microspheres: Dry the hollow microspheres at 150-200℃ for 2-4 hours to obtain dried hollow microspheres;

[0027] Step 2: Preparation of modified resin: Heating bisphenol A type epoxy resin to 60-80℃, adding active silica alumina oxide, and continuing the reaction for 1-2 hours to obtain a modified resin with a core-shell structure; wherein, the mass ratio of bisphenol A type epoxy resin to active silica alumina oxide is (2~4):1;

[0028] Step 3, Mixing: Place the dried hollow microspheres, modified resin, nano-reinforcing material and coupling agent into a mixer and mix at 2000-3000 r / min for 10-20 minutes to ensure that each component is evenly distributed and fully coated to obtain a mixture.

[0029] Step 4: Activation treatment: Heat-treat the mixture at 180-220℃ for 30-60 minutes, cool it, crush and sieve it to obtain the above-mentioned composite oil well cement slurry weight-reducing agent.

[0030] The raw materials in this application are not simply mixed. After mixing, the materials are heat-treated to allow one end of the coupling agent to bond with inorganic materials (cement, microspheres) and the other end to aggregate with modified resin. At the same time, the heat treatment promotes the cross-linking reaction of the modified resin itself and the reaction between the resin and active silica-alumina oxide. In addition, the hollow microspheres are tightly coated by the modified resin and nano-reinforcing materials, giving them a lower density while having higher mechanical strength and stability.

[0031] An application of a composite oil well cement slurry weight-reducing agent as an additive in cement slurry: Based on 100 parts by weight of cement in the cement slurry, adding 20-40 parts of the aforementioned composite oil well cement slurry weight-reducing agent results in a cement slurry density of 1.20-1.60 g / cm³. 3 It is used for cementing operations in oil wells in low-pressure, easily leaking formations and long cementing sections.

[0032] The cement slurry has the following characteristics: API filtration loss ≤50mL, fluidity ≥18cm, and density difference between the upper and lower parts of the slurry ≤0.03g / cm³. 3 It has a 24-hour compressive strength greater than 15 MPa, adjustable thickening time, and temperature resistance up to 180℃. This cement slurry is particularly suitable for the full well sealing requirements in high and medium risk areas of the Shaanxi North Gas Field, as well as cementing operations in long sealing sections and weak, easily leaking formations.

[0033] The technical solution of the present invention achieves the following beneficial technical effects:

[0034] 1. Synergistic Effect: The modified resin in the composite oil well cement slurry weight-reducing agent of this invention is prepared by reacting bisphenol A type epoxy resin with active silica-alumina oxide, wherein the active silica-alumina oxide is prepared by tetraethoxysilane (TEOS) and aluminum nitrate via a sol-gel method. The prepared active silica-alumina oxide has a large specific surface area, forming an atomically dispersed Si-O-Al three-dimensional network structure. The surface of the active silica-alumina oxide has relatively uniform active groups of silanol and aluminum hydroxyl groups, which can chemically bond with the epoxy groups of the epoxy resin during the reaction process, forming a strong covalent bond connection and a core-shell structure. This enhances the interfacial bonding force between the inorganic material and the organic resin, effectively transferring stress. When the modified resin fills the voids or surface between hollow microspheres, it greatly improves the temperature resistance, compressive strength, flexural strength, and other mechanical properties of the cement paste; it also improves the bonding force between the hollow microspheres and the cement matrix, thus ensuring the reliability of the modified resin as a binder coating the surface of the hollow microspheres and as a reinforcement of the system density. Adding only bisphenol A epoxy resin can enhance its strength to some extent, but bisphenol A epoxy resin has low heat resistance, which will affect the high-temperature stability of subsequent cement grout to some extent.

[0035] This method employs a sol-gel process to hydrolyze and polymerize silicon and aluminum sources in solution, forming active silicon-aluminum oxides with a uniform Si-O-Al three-dimensional network structure. The resulting material exhibits a highly uniform amorphous structure and abundant, evenly distributed active sites (silanol and aluminum hydroxyl groups). Furthermore, this method achieves a high specific surface area and porous structure, significantly enhancing material transport and adsorption capabilities. This allows the active silicon-aluminum oxides prepared by this method to readily form strong interfacial bonds with resins or cement slurries, exhibiting performance far superior to silicon-aluminum oxides bonded to resins prepared by simple mechanical mixing or conventional calcination methods.

[0036] 2. Combining low density and high strength: Through a multi-stage, tightly packed particle design, the density is reduced while maintaining the strength of the cement stone. The density is 1.25 g / cm³. 3 After being cured at 80℃ for 48 hours, the cement stone can achieve a compressive strength of over 12MPa and a density of 1.40-1.60g / cm³. 3 The 24-hour compressive strength of the cement stone is greater than 15 MPa.

[0037] 3. Excellent slurry stability: The nano-reinforcing material effectively fills the gaps between the hollow microspheres and modified resin, further optimizing the packing density and achieving close packing. Simultaneously, the nano-reinforcing material can significantly improve the long-term strength of the cement paste through a pozzolanic reaction during cement hydration. One end of the coupling agent molecule bonds to the inorganic materials (cement, microspheres), and the other end bonds to the organic materials (resin), improving the interfacial bonding force between components and preventing delamination.

[0038] The synergistic effect of nano-reinforcing materials and coupling agents significantly improves the settling stability of cement slurry, with a density difference of less than 0.03 g / cm³. 3 It is far below the industry standard (0.06g / cm³). 3 ).

[0039] 4. Wide adaptability: The composite weight-reducing agent can adapt to bottom hole temperatures of 30℃ to 200℃ and can be well compatible with various admixture systems (such as fluid loss reducers, dispersants, etc.) to meet the needs of different well conditions.

[0040] 5. Good engineering applicability: The low-density cement slurry, formulated with composite lightweight materials based on the close packing theory, has good stability and strong corrosion resistance, effectively solving the problems of cementing quality and oil and gas reservoir protection in low-pressure, easily leaking, and long cementing sections.

[0041] 5. Excellent cost-effectiveness: It uses low-cost material compounding, which greatly reduces material costs. At the same time, the preparation process is simple and suitable for large-scale production. Detailed Implementation

[0042] I. A method for preparing a composite oil well cement slurry weight-reducing agent, comprising the following steps:

[0043] 1. Pretreatment of hollow microspheres:

[0044] Selected hollow microspheres (bulk density 0.75 g / cm³) 3 Place them in an oven and dry at 180℃ for 3 hours to remove adsorbed moisture and improve adhesion to the resin, thus obtaining dried hollow microspheres.

[0045] 2. Preparation of modified resin:

[0046] Add 100 kg of bisphenol A type epoxy resin to the reactor, heat to 60-80℃, then add 30 kg of active silicon aluminum oxide, and react for 1.5 hours; discharge and cool, then pulverize to below 100 mesh to obtain modified resin.

[0047] The active silica-alumina oxide is prepared by a sol-gel method using tetraethoxysilane (TEOS) and aluminum nitrate, wherein the mass ratio of tetraethoxysilane to aluminum nitrate is 5:1.

[0048] Specifically, tetraethoxysilane was dissolved in anhydrous ethanol (anhydrous ethanol to TEOS volume ratio 2:1) to obtain precursor solution A; aluminum nitrate was dissolved in deionized water (deionized water to aluminum nitrate mass ratio 10:1) to obtain precursor solution B. The mixture was stirred in a water bath at 30-35℃ at a stirring rate of 300 rpm. Precursor solution B was added dropwise to precursor solution A at a rate of 1-2 ml / min. After the addition was complete, the temperature was raised to 40℃ and reacted for 1-2 hours to obtain a sol. The sol was then poured out and allowed to stand at 40℃ for 6-12 hours, followed by drying at 100℃ to form a solid gel. The solid gel was then placed in a calcination furnace and calcined at 600-700℃ for 2-4 hours. After cooling, a white, loose, active silica-alumina oxide powder was obtained.

[0049] 3. Preparation of composite weight-reducing agents:

[0050] Take 40 kg of dried hollow microspheres, 25 kg of modified resin, 30 kg of nano-reinforcing material (the weight ratio of nano-SiO2 and Al2O3 is 1.5:1) and 5 kg of γ-aminopropyltriethoxysilane as a coupling agent and add them to a mixer; mix at 2500 r / min for 15 minutes to ensure that each component is evenly distributed and fully coated on the surface to obtain a mixture.

[0051] The mixture is transferred to a heat treatment furnace and treated at 200°C for 45 minutes to allow the components to undergo a coupling reaction and react into a homogeneous product. After cooling, the product is pulverized by a ball mill and passed through a 200-mesh sieve to obtain a composite oil well cement slurry lightening agent.

[0052] II. Performance Testing

[0053] To verify the performance of the composite oil well cement slurry weight-reducing agent of the present invention, the following tests were conducted:

[0054] Experiment 1: Cement grout preparation and basic properties

[0055] Take 10 kg of Grade G oil well cement, 3 kg of the composite oil well cement slurry weight-reducing agent of this invention, 8 kg of water, 0.06 kg of fluid loss reducing agent, and 0.03 kg of retarder, and prepare the cement slurry according to the API standard procedure. The test results are as follows (the comparative example is a low-density cement slurry from a domestic cement plant):

[0056] Table 1: Basic Properties of Cement Grout

[0057]

[0058] Experiment 2: Mechanical properties of cement stone

[0059] Cement slurry prepared with the above-mentioned cement slurry weight-reducing agent and low-density cement slurry from a domestic cement plant were poured into molds and cured in a 90℃ water bath for 24 hours. Mechanical properties were then tested.

[0060] Table 2: Mechanical Properties of Cement Stone

[0061]

[0062] Experiment 3: High Temperature Stability Test

[0063] The cement slurry prepared with the above-mentioned cement slurry lightening agent and a low-density cement slurry from a domestic cement plant were aged in a 180℃ high-temperature roller heating furnace for 4 hours, and their performance was tested.

[0064] Table 3: Performance changes after high-temperature aging

[0065]

[0066] The test results show that the cement slurry prepared using the composite oil well cement slurry weight-reducing agent of this invention maintains low density while having excellent mechanical properties and high-temperature stability, fully meeting the cementing requirements of deep wells, ultra-deep wells and complex formations.

[0067] III. Field Application

[0068] The composite oil well cement slurry weight-reducing agent of this invention has been field-tested and applied in blocks such as Daqing Gas Field, Changqing Oil Field, Jilin Oil Field, and Rumaila Oil Field in Iraq by China National Petroleum Corporation. In the Daqing Oil Field's No. 1 and No. 2 Oil Production Plants, the low-density cement slurry prepared with this composite oil well cement slurry weight-reducing agent has effectively solved the problems of low pressure, easy leakage, long cementing sections, cementing quality, and oil and gas reservoir protection, with good application results.

[0069] In summary, the composite oil well cement slurry weight-reducing agent provided by this invention, based on the close packing theory, achieves a balance of low density, high strength, and high stability in oil well cement slurry through the rational proportioning and synergistic effect of hollow microspheres, modified resin, nano-reinforcing materials, and coupling agents. This composite oil well cement slurry weight-reducing agent has a simple preparation process, readily available raw materials, and low cost, making it suitable for industrial production and possessing broad prospects for application in the oilfield cementing field.

[0070] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of the claims of this patent application.

Claims

1. A composite oil well cement slurry reducer characterized by, Components comprising the following weight parts: hollow microsphere 20~40 parts, modified resin 15~25 parts, nano-enhancing material 25~30 parts and coupling agent 3~8 parts; The modified resin is prepared by reacting bisphenol A type epoxy resin with active silicon aluminum oxide.

2. The composite oil well cement slurry weighting agent of claim 1, wherein, The active silicon-aluminum oxide has a Si-O-Al three-dimensional network structure, and the specific surface area of the active silicon-aluminum oxide is 300-600 m 2 / g, and the pore size is 2-10 nm.

3. The composite oil well cement slurry weighting agent according to claim 1 or 2, characterized in that, The active silicon aluminum oxide is prepared by sol-gel method from tetraethoxysilane and aluminum nitrate, wherein the mass ratio of tetraethoxysilane to aluminum nitrate is (4~6):

1.

4. The composite oil well cement slurry weighting agent of claim 3, wherein, The sol-gel method specifically comprises: S1, mixing tetraethoxysilane and anhydrous ethanol according to a volume ratio of 1:(2~4) to obtain A precursor solution; S2, mixing aluminum nitrate and deionized water according to a mass ratio of 1:(9~11) to obtain B precursor solution; S3, at 30-35℃, drop B precursor solution into A precursor solution, after drop completion, increase the temperature to 40~45℃, react for 1-2 hours to obtain sol; S4, after pouring out the sol, place it at 40-45℃ for aging, dry it at 80~120℃ to form solid gel, then calcine it at 600-700℃ to obtain active silicon aluminum oxide.

5. The composite oil well cement slurry weighting agent of claim 1, wherein, The hollow microbeads are one or more of float beads, glass microbeads and ceramic microbeads; the bulk density of the hollow microbeads is 0.60-0.90 g / cm 3 , and the pressure-bearing capacity is ≥ 70 MPa.

6. The composite oil well cement slurry weighting agent of claim 1, wherein, The average particle size of the hollow microsphere is 40-80μm; the average particle size of the modified resin is 10-20μm; The average particle size of the nano-enhancing material is 0.01-0.1μm; the volume ratio of the hollow microsphere, the modified resin and the nano-enhancing material is (8-10):(1-2):(2-2.5).

7. The composite oil well cement slurry weighting agent of claim 1, wherein, The coupling agent is silane coupling agent, and the silane coupling agent is γ-aminopropyl triethoxysilane or γ-glycidyl ether propyl trimethoxysilane.

8. The composite oil well cement slurry weighting agent of claim 1, wherein, The nano-enhancing material is a composite of nano-silicon dioxide and nano-aluminum oxide, and the weight ratio of nano-silicon dioxide to nano-aluminum oxide in the nano-enhancing material is (1-2):1, and the specific surface area of the nano-enhancing material is ≥200m² / g.

9. A method of preparing a composite oil well cement slurry reducer, characterized by, The method comprises the following steps: Step one, hollow microsphere pretreatment: dry the hollow microsphere at 150-200℃ for 2-4 hours to obtain dried hollow microsphere; Step two, prepare modified resin: heat bisphenol A type epoxy resin to 60-80℃, add active silicon aluminum oxide, and continue to react for 1-2 hours to obtain modified resin with core-shell structure; wherein the mass ratio of bisphenol A type epoxy resin to active silicon aluminum oxide is (2~4):1; Step three, mix: put the dried hollow microsphere, modified resin, nano-enhancing material and coupling agent into a mixer, mix at a speed of 2000-3000r / min for 10-20 minutes to obtain mixed material; Step four, activation treatment: heat the mixed material at 180-220℃ for 30-60 minutes, cool it, crush it and sieve it to obtain the composite oil well cement slurry reducing agent according to any one of claims 1~8.

10. Use of a composite oil well cement slurry reducer as an additive in a cement slurry, characterized in that, The composite oil well cement slurry reducing agent of any one of claims 1-8 is added in an amount of 20-40 parts by weight based on 100 parts by weight of cement in the cement slurry to prepare a cement slurry with a density of 1.20-1.60 g / cm 3 for use in oil well cementing operations in low-pressure and leaky formations and long cementing sections.